Adverse drug reactions in West Africa - Cliff-Eribo, Kennedy O. (2016)
Adverse drug reaction (ADR) reports of countries varies due to differences in the prevalence of diseases and hence the types of drugs used. ADRs are a major health and economic burden worldwide. National health authorities monitor the safety of medicines to protect consumers from the hazards of drugs. ADR databases are also maintained from where reports are regularly evaluated to detect signals of new ADRs and determine the increase of those already known. A review of paediatric and general population studies conducted on ADRs from national ADR databases was carried out. The majority of studies identified were from countries in Europe and North America, and only one study on the general population was conducted from the Ethiopian ADR database in Africa. No paediatric study was identified in Africa. Skin reactions associated with antiretroviral drugs were the most frequent ADRs in the study conducted from the Ethiopian ADR database. Anti-infective agents, mostly vaccines, were mostly associated with the ADRs in children in Europe and Latin America, and drugs used for treating attention deficit hyperactivity disorders (ADHD) were implicated with the ADRs reported for children in North America.